Intensive Mentoring Approach to Enhance Qur’anic Literacy and Prayer Memorization in Secondary Schools - Dwi Vira Ampesi; Euis Rina Handayani; Nur Azizah; Adelia Rizky Januari; Hermanto (Faculty of Education and Teaching Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2025)
This study aims to analyze the effectiveness of an intensive mentoring approach in improving Qur’anic literacy and prayer memorization among secondary school students at STKIP Muhammadiyah Arar Labschool High School, Sorong Regency. The research addresses the persistent gap between curriculum expectations and students’ actual competencies, where more than half of the students were still at the Iqra’ level upon entering high school. A qualitative descriptive design was employed, with data collected through non-participant observation, semi-structured interviews, and documentation. Data were analyzed using the Miles and Huberman model, including data reduction, display, and conclusion drawing, supported by source triangulation to ensure credibility. The findings indicate substantial improvement after two months of daily 30-minute mentoring sessions conducted before formal classes. Of 39 students, 43.6% achieved fluent Qur’anic reading, 38.5% became fairly fluent, and 43.6% fully memorized the targeted prayer recitations, while 51.3% entered the early memorization stage. The program also fostered non-cognitive outcomes, including increased discipline, confidence, punctuality, and religious motivation. The novelty of this study lies in its integrated dual-focus model that combines Qur’anic reading progression, structured prayer memorization, individualized deposit-and-journal monitoring, and tajwid micro-sessions within a daily school routine. This study contributes theoretically by advancing a holistic mentoring framework and practically by offering a low-cost, replicable model for strengthening Qur’anic literacy and worship competence in secondary education.